Menschen, die ich kannte Erinnerungen eines Achtzigjährigen - Davidsohn, Robert (Deutsche Geschichtsquellen des 19. und 20. Jahrhunderts (DGQ), 2020)
»Robert Davidsohn (1853-1937). People I knew - Memories of an Octogenarian« The book presents the annotated edition of the memoir of Robert Davidsohn (1853-1937), a German-Jewish scholar, still known for his history of Medieval Florence. The autobiography is the document of a life between Germany and Italy, of a man who after a career as a journalist and a newspaper publisher in ›Kaiserreich‹ Berlin, chose to become an independent historian living in Florence and gaining international academic recognition, and, as an old man, had to confront the triumph of Fascism and Nazism.